Unsinkable - Nakhai, Shasha; Williamson, Rich (Canada, 2012)
The documentary films a floating restaurant that has been a Toronto landmark for over 40 years, to reveal a charming old man with a lifelong passion for his boat, decades of selfless community service and an infectious joie de vivre.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films